SOUTH SHORE MARKETING STRATEGY DURING THE ADAPTATION PERIOD FOR NEW HABITS IN THE SPECIAL REGION OF YOGYAKARTA - Lenny Kurnia Octaviani; Muhammad Zadegh Amalulahli; Deni Dwi Ananti (Kepariwisataan: Jurnal Ilmiah, 2022)
South Shore is a Tourism Destination located in Tepus District, Gunung Kidul, Special Region of Yogyakarta. The aim of this research is to identify the marketing potentials that can be developed in the new Habit Adaptation Era. This type of research is conducted in this study using a qualitative approach, while the analysis technique used is using a SWOT analysis. As an object that is managed by a private ownership, there are many shortcomings that are found when the community is doing tourism activity in the South Shore. Therefore, a Marketing Strategy is needed to maximize the revenue found in this Tourism Destination. The results of this study indicate that it is necessary to improve the management of the COVID-19 pandemic reading so that tourists feel satisfied to carry out tourism activities in this tourism destination.Keywords: South Shore, Tourism Destination, Marketing Strategy, Covid-19 Pandemic